REFLECTION OF NARCISSISM ON NEF’î’S POEMS - YALÇIN, İdris; BOZKURT, Kenan (Atlas Journal, 2020)
Approaching literary works with a psychological viewpoint and analyzing these works with psychoanalytic method started with Freud and were developed by subsequent psychologists. With the help of psychoanalytic review method, the depth of unconscious has been reached based on artists’ lives, and determinations on the creation process of literary works have been made. What is depicted in literary works is analyzed with that method. Narcissism has an important role in these analyses. “Narcissism”, which is used for determining character today, is named after young and handsome Narkisos, who -in Greek mythology- falls in love with his reflection on water, that is himself, and falls into the water trying to reach it and drowns. Narcissism, a kind of defence mechanism that one develops against his/her insufficiency, is an aim of drawing the whole attention to himself/herself. The usual narcissist personality traits appear as boasting in poems. While it is possible to describe boastings of classic poets as boast, praise, egocentrism and ego, when it comes to boasting, no one among divan poets exceeded as much as Nef’î , expressing megalomaniac manner so high-pitched. The poet’s regarding himself superior to other poets, boasting about himself and being eaten up with pride are basic traits of his narcissist personality. In this regard, Nef’î, who comes into prominence with his fahriyye works, appears as a character having all traits of narcissism. It is essential to look at his early childhoodfor the reasons of reflection of narcissism, a personality disorder, on Nef’î’s poems. Although the poems of Nef’î, a 17th century poet, were written centuries before the rise and development of psychoanalysis, it is possible to read and analyze these poems based on narcissism. In this study, Nef’î’s narcissist side is going to be tried to be revealed by looking at Nef’î’s life, personality and poems, in an aim of analyzing his poems based on “narcissism”, which is included in the field of study of psychoanalysis, and the psychologic reasons of the incoherence in his style is going to be emphasized.